The Main Points of Political Thought of Sheikh Isma'il Mahallati in Constitutionalism Discourse - hamid saeedijavadi; aliakbar amini (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2020)
Sheikh Ismail Mahallati, known as a modernist scholar in Najaf, supported and defended the constitution with the beginning of the constitutional movement and after its establishment in Iran, along with other prominent scholars of that seminary, such as Akhund Khorasani, Mazandarani, Naeini and Tehrani. Coinciding with the establishment of the first term parliament and about a year before of Naini's book "Tanbih-al-ummah and Tanzih-al-mellah", he wrote a treatise entitled "Leali al-Marbutah in the Necessity of the Constitution", all of which was in defense of the Constitution and in response to its religious opponents. Sheikh Ismail Mahallati's main concern was how to overthrow the authoritarian regime and then control and monitor the government's performance. The discourse of local political thought in this treatise is formed around three basic axes: limiting the power, power of the nation and religion and rationality. Each of the above three components have elements that can be combined to overlap the nature of each component. In total, these components have eleven basic elements. With a historical and analytical approach, this article seeks to explain various aspects of neighborhood political thought in defense of the Iranian constitutional movement.